Evaluation of smartphone APP-based case-management services among antiretroviral treatment-naïve HIV-positive men who have sex with men: a randomized controlled trial protocol - Xiaoyan Fan; Rui She; Cong Liu; Haidan Zhong; Joseph T. F. Lau; Chun Hao; Jinghua Li; Yuantao Hao; Linghua Li; Jing Gu (BMC, 2020)
Abstract Background Men who have sex with men (MSM) are disproportionally affected by HIV in China. 'Treatment as Prevention' is a promising strategy for HIV prevention but requires adequate adherence. Mobile health (mHealth) may be an acceptable and feasible approach for service delivery, but there is little evidence supporting mHealth intervention for improving antiretroviral treatment adherence among HIV-infected MSM in low- and middle-income countries, including China. This study will aim to develop a smartphone application-based case-management service and compare its efficacy to standard care with regards to adherence, CD4, HIV viral load and psychosocial outcomes among MSM patients in Guangzhou, China. Methods A non-blinded 1:1 parallel-group randomised controlled trial will be conducted in Guangzhou Eighth People's Hospital, with 300 MSM enrolled in each arm. Eligible MSM who are newly initiating ART will be randomly assigned to an intervention group (standard-of-care case management plus mHealth intervention) or a control group (standard-of-care case management). The development of the mHealth intervention will be based on the information-motivation-behavioural skills theory of ART adherence, and comprise four components: educational articles, one-to-one online communication with case managers, support-service information and hospital-visit reminders. Outcome measures will be collected at baseline and at months 1, 3, 6, and 12. The primary outcomes will be ART adherence and CD4 count at month 6. Secondary outcomes include HIV RNA, sexual behaviours, mental health status, illness perceptions, and quality of life. χ 2 test and t-test will be used for between-group comparisons. Intervention effects will be evaluated using General estimating equation performed by SAS 9.0, on the principle of intention-to-treat. Structural equation modelling will be used to test potential mechanisms of intervention effect. Discussion This study is the first to explore the efficacy of mHealth intervention in the case management services targeted at HIV-infected MSM in low-and middle-income countries. Once proven effective, the innovative mHealth service could be integrated into the routine case management of PLWH. as well as be tailored to the patient management service for other chronic conditions. Trial registration ClinicalTrial.gov: NCT03860116; Registered on 1 March 2019.